From the editor - Bukh, Vladimir (project baikal, 2005)
During the time of total standard expansion the architects, except those few working for the institutions of standard engineering, were not involved in housing design. There was no need to engage many architects, taking into account stable standard regulations of the types 445 (according to the number of habitable rooms) of flats. Working out of individual projects was ordered by Moscow and bore exclusive nature. The professional school was degrading. Then, all of a sudden, the state monopoly collapsed, and the building business was filled by a flow of unskilled employees, who now have to learn from their personal experience and to master this most complicated type of architectural and building craft. The usable area of a standard flat was calculated up to the fractions of a square meter. Now, when the builder and the architect became face to face with each other, and the first one does not quite know what he wants, and the second one 4 what he can, a number of square meters of unusable area are freely roaming around the flats, being passed off as an elite feature. The sense of planning and the pleasure in this occupation will come in the course of time, in the second turn though, because now, in revenge on the standard austerity, the creative fancies are usually performed on the facades. And it often seems that a standard house is more honest and perfect with respect to the great architecture than the today's individual one.Houses are built rarely and they are expensive in Irkutsk. It is impossible to penetrate into the oddity of such «market». The building business satisfies status quo. And the rest is all right.